MENTAL HEALTH DISORDERS AMONG HEALTHCARE WORKERS AFTER THE COVID-19 PANDEMIC - Luigi La Via (Euromediterranean Biomedical Journal)
The COVID-19 pandemic had a great impact on the mental health of healthcare workers (HCW) worldwide. Studies have reported a high prevalence of anxiety, depression, insomnia, and post-traumatic stress disorder among HCWs, with frontline workers experiencing higher rates of mental health issues. This comprehensive review focuses on the prevalence of mental health problems among HCWs in the aftermath of the pandemic, discussing contributing factors and examining interventions. Factors leading to this increased prevalence include increased workload, high levels of stress, lack of personal protective equipment, stigmatization, and pre-existing mental health disorders. Initiatives to improve the mental health of HCWs may include providing psychosocial support, strengthening organizational backing, offering appropriate training and education, implementing flexible work schedules, conducting mental health screenings, and encouraging self-care practices. Further research is needed to understand long-term outcomes, factors influencing resilience, vulnerability and the impact on HCWs in different settings.